Books as an element of social communication in Russian-Ukrainian War - Kovalchuk, Iryna (Current issues of Ukrainian linguistics: theory and practice, 2024)
The article* analyzes the role of books in social communication that is conducted at the interstate level at the wartime, taking as an example the humanitarian project "Ukrainian Bookshelf" initiated by Olena Zelenska, the First Lady of Ukraine. The aim of the article is to describe a book as a social-communicative phenomenon, outline how social communication occurs at the interstate level, and to characterize the elements of such communication according to Lasswell's model of communication. The article examines the elements and participants of communication about library projects, describing its main features at the institutional level. The project "Ukrainian Bookshelf" provides convincing data for the research as it has collected over 47,000 books in Ukrainian and translations and 190 Ukrainian bookshelves have been opened in 46 countries worldwide. Statistical data are provided for 22 countries where Ukrainians have been forced to relocate due to Russian aggression. The article examines the motivation of the Ukrainian state to deploy and support communication about Ukrainian literature in the situation when it faces existential challenges. The article describes the communicator and two types of communication recipients, namely foreign political and intellectual elites as well as millions of Ukrainian citizens, mostly women and children, who have become refugees. It is proved that the book becomes a channel of communication and its message. Ukrainian experience shows that books collection, organization of libraries, and arrangement of bookshelves can be the result of private and volunteer initiatives. Shelves are created not only in national and university libraries but also in places frequently visited by Ukrainians: cafes, information centers, temporary accommodation facilities for refugees, language courses, integration programs, private enterprises, and cultural and community spaces. It is assumed that humanitarian literary and library projects can become educational activism, offer readers a reflection on war and peace, and contribute to the formation and strengthening of the nation unity. * Researcher at the project "Imaginative Literature and Social Trust, 1990-2025"
Keywords: social communication, Russian-Ukrainian war, Ukrainian books, library project, Lasswell's model of communication.